DEVELOPMENT AND DISSEMINATION OF AGRICULTURAL TECHNOLOGIES TO SOME COMMUNITIES IN NIGERIA - ADEBOWALE, E. A.; OBATOLU , V. A.; AYOOLA, O. T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The Institute of Agricultural Research and Training (l. A, R, & T.), Obafemi Awolowo University. Ibadan has made tremendous achievements towards increasing food production and alleviating poverty within the farming communities by using a Unified Agricultural Extension System (UAES) and Training & Visit (T&V) approach. The V approach entails a renewed focus with emphasis on farm visits, regular field supervision, concentration of efforts and research extension-farmers-linkage system (REFILS). The Institute has been able to develop and disseminate improved agricultural technologies to many communities in the country. These developments have been in the area of organic-based fertiliser and breeding of new crop varieties that are resistance to diseases and adaptable to different ecological zones. Breakthroughs have also been recorded in improved conventional and unconventional livestock management. Of importance are snail breeding and cane rat domestication. Other improved technologies developed by the Institute are in the area of designing, fabrication and evaluation of agricultural equipment and gender specific technologies including food processing and utilisation. All these technologies have been successfully disseminated to many communities within the country.